MicroRNA-145 Regulates Pathological Retinal Angiogenesis by Suppression of TMOD3 - Chi-Hsiu Liu; Zhongxiao Wang; Shuo Huang; Ye Sun; Jing Chen (Elsevier, 2019)
Pathological angiogenesis is a hallmark of various vascular diseases, including vascular eye disorders. Dysregulation of microRNAs (miRNAs), a group of small regulatory RNAs, has been implicated in the regulation of ocular neovascularization. This study investigated the specific role of microRNA-145 (miR-145) in regulating vascular endothelial cell (EC) function and pathological ocular angiogenesis in a mouse model of oxygen-induced retinopathy (OIR). Expression of miR-145 was significantly upregulated in OIR mouse retinas compared with room air controls. Treatment with synthetic miR-145 inhibitors drastically decreased levels of pathological neovascularization in OIR, without substantially affecting normal developmental angiogenesis. In cultured human retinal ECs, treatment with miR-145 mimics significantly increased the EC angiogenic function, including proliferation, migration, and tubular formation, whereas miR-145 inhibitors attenuated in vitro angiogenesis. Tropomodulin3 (TMOD3), an actin-capping protein, is a direct miR-145 target and is downregulated in OIR retinas. Treatment with miR-145 mimic led to TMOD3 inhibition, altered actin cytoskeletal architecture, and elongation of ECs. Moreover, inhibition of TMOD3 promoted EC angiogenic function and pathological neovascularization in OIR and abolished the vascular effects of miR-145 inhibitors in vitro and in vivo. Overall, our findings indicate that miR-145 is a novel regulator of TMOD3-dependent cytoskeletal architecture and pathological angiogenesis and a potential target for development of treatments for neovascular eye disorders. Keywords: angiogenesis, endothelial cell, microRNA, miR-145, neovascularization, retinopathy, Tmod3